Innovations in the Cement Industry: Advancing Towards Sustainable Concrete Production - Rahman, Herliati; Rizqy F, Muhammad (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2024)
Slag, an artificial pozzolan derived from the by-product of metal ore smelting, exhibits notable richness in active silica and alumina. This investigation scrutinizes the influence of slag as a clinker substitute on cement quality. The study explores the composition range of slag from 15.69% to 20.39% of the total cement mass. Other constituent materials, including gypsum (2.07%), limestone (17.24-22.54%), and clinker (55-65%), are compared with commercial cement available in the market, featuring 73.09% clinker, 2.07% gypsum, 11.89% limestone, and 12.95% trass. The study employs rigorous physical tests, encompassing Blaine, residue at 45 m (325 mesh), flowability, setting time, and compressive strength assessments at 1, 3, 7, and 28 days. The Blaine testing, the residue at 45 m, and other tests were conducted meticulously to ensure the accuracy and reliability of the results. Blaine testing measured specific surface area, residue at 45 m assessed fineness, flowability evaluated paste workability, setting time determined paste stiffness, and compressive strength assessed material durability. All tests followed ASTM standards, providing reliable insights into cement performance. Compared to the commercial sample, there is a decrease in compressive strength in all results with an increase in the amount of slag. This condition is because components such as tricalcium silicate (C3S) and dicalcium silicate (C2S), which play a crucial role in producing hydration strength, decrease with the reduction of clinker. However, the compressive strength specified by ASTM C 109/109M-01 280 kg/m2 standard is still exceeded. Optimal results are obtained with a slag substitution of 16.64%, resulting in compressive strength of 305 kg/m2 at 28 days. This investigation highlights slag as a promising substitute for clinker in cement production due to its high silica content. Slag offers several advantages, including enhanced sustainability by reducing environmental impact and lowering production costs. Its utilization diversifies raw material sources, promoting industry resilience.